Alzheimer's Pathology Is Associated with Dedifferentiation of Intrinsic Functional Memory Networks in Aging. (25th May 2021) - Cassady, Kaitlin E; Adams, Jenna N; Chen, Xi; Maass, Anne; Harrison, Theresa M; Landau, Susan; Baker, Suzanne; Jagust, William
Abstract: In presymptomatic Alzheimer's disease (AD), beta-amyloid plaques (Aβ) and tau tangles accumulate in distinct spatiotemporal patterns within the brain, tracking closely with episodic memory decline. Here, we tested whether age-related changes in the segregation of the brain's intrinsic functional episodic memory networks—anterior-temporal (AT) and posterior-medial (PM) networks—are associated with the accumulation of Aβ, tau, and memory decline using fMRI and PET. We found that AT and PM networks were less segregated in older than that in younger adults and this reduced specialization was associated with more tau and Aβ in the same regions. The effect of network dedifferentiation on memory depended on the amount of Aβ and tau, with low segregation and pathology associated with better performance at baseline and low segregation and high pathology related to worse performance over time. This pattern suggests a compensation phase followed by a degenerative phase in the early, preclinical phase of AD.